Power system virtual inertia implemented by thermostatically controlled loads - Zhe Wang; Yu-Qing Bao; Hui-Fang Di; Hui-Fang Di (IET Smart Grid, 2020)
It can be foreseen that the modern electric power system tends to have an increasing penetration of renewable energy sources (RESs) and controllable loads under ancillary services programmes, which will cause the power system inertia reduction. For the thermostatically controlled loads (TCLs) (e.g. air conditioners) have large potentials for providing ancillary services for power systems and are more flexible and cost-efficient than traditional energy storage system, in this study, an approach of modelling power system virtual inertia (VI) by TCLs is proposed, while maintaining customers’ comfort level. Considering the TCLs’ heterogeneous characteristic and response uncertainty, a load tracking control strategy based on proportional–integral controller is proposed to preserve the performance of VI control strategy. Besides, the coefficient [inline-formula] is put forward for the first time to quantify and analyse the conversion efficiency between kinetic energy and thermal energy. Then, the method to design [inline-formula] based on the energy analysis is presented. Finally, some simulation results are provided to verify the effectiveness of the control scheme.